Characterization of new cristamonad species from kalotermitid termites including a novel genus, Runanympha - Racquel A. Singh (Nature Portfolio, 2021)
Abstract Cristamonadea is a large class of parabasalian protists that reside in the hindguts of wood-feeding insects, where they play an essential role in the digestion of lignocellulose. This group of symbionts boasts an impressive array of complex morphological characteristics, many of which have evolved multiple times independently. However, their diversity is understudied and molecular data remain scarce. Here we describe seven new species of cristamonad symbionts from Comatermes, Calcaritermes, and Rugitermes termites from Peru and Ecuador. To classify these new species, we examined cells by light and scanning electron microscopy, sequenced the symbiont small subunit ribosomal RNA (rRNA) genes, and carried out barcoding of the mitochondrial large subunit rRNA gene of the hosts to confirm host identification. Based on these data, five of the symbionts characterized here represent new species within described genera: Devescovina sapara n. sp., Devescovina aymara n. sp., Macrotrichomonas ashaninka n. sp., Macrotrichomonas secoya n. sp., and Macrotrichomonas yanesha n. sp. Additionally, two symbionts with overall morphological characteristics similar to the poorly-studied and probably polyphyletic ‘joeniid’ Parabasalia are classified in a new genus Runanympha n. gen.: Runanympha illapa n. sp., and Runanympha pacha n. sp.